Critical care bed capacity in Asian countries and regions - Phua, Jason; Faruq, Mohammad Omar; Kulkarni, Atul P; Ike Sri, Redjeki; Khamsay, Detleuxay; Naranpurev, Mendsaikhan; Kyi Kyi, Sann; Babu Raja, Shrestha; Jose Emmanuel M, Palo; Rashan, Haniffa; Chunting, Wang; Madiha, Hashmi; et al. (Lippinkott Williams and Wilkins, 2020)
Objective: To assess the number of adult critical care beds in Asian countries and regions in relation to population size. Design: Cross-sectional observational study. Setting: Twenty-three Asian countries and regions, covering 92.1% of the continent’s population. Participants: Ten low-income and lower-middle–income economies, five upper-middle–income economies, and eight high-income economies according to the World Bank classification. Interventions: Data closest to 2017 on critical care beds, including ICU and intermediate care unit beds, were obtained through multiple means, including government sources, national critical care societies, colleges, or registries, personal contacts, and extrapolation of data. Measurements and Main Results: Cumulatively, there were 3.6 critical care beds per 100,000 population. The median number of critical care beds per 100,000 population per country and region was significantly lower in low- and lower-middle–income economies (2.3; interquartile range, 1.4–2.7) than in upper-middle–income economies (4.6; interquartile range, 3.5–15.9) and high-income economies (12.3; interquartile range, 8.1–20.8) (p = 0.001), with a large variation even across countries and regions of the same World Bank income classification. This number was independently predicted by the World Bank income classification on multivariable analysis, and significantly correlated with the number of acute hospital beds per 100,000 population (r2 = 0.19; p = 0.047), the universal health coverage service coverage index (r2 = 0.35; p = 0.003), and the Human Development Index (r2 = 0.40; p = 0.001) on univariable analysis. Conclusions: Critical care bed capacity varies widely across Asia and is significantly lower in low- and lower-middle–income than in upper-middle–income and high-income countries and regions.